Findbuch des Bestandes Abt. 22: Herzöge von Schleswig-Holstein-Sonderburg-Augustenburg - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2012)
The Augustenburg Duke's lineage (house) rose in the 17th century as a side line of the Princely House of Schleswig-Holstein-Sonderburg. It expired in 1931 in male line. Dept. (Abt.) 22 comprises the Ducal-Augustenburg House Archives (Primkenauer Archive) and the archives of the family branch of the Ducal house residing in Gut Noer. The period of existence extends from the 17th to the 20th century, with a focus on the 19th century. Particularly noteworthy is the extraordinarily important archive material from the period of Schleswig-Holstein's political history, especially concerning foreign and military affairs. In addition, Abbot 22 also contains the archives of the Ducal Government of Schleswig-Holstein (1863-1866). A common register of places, subjects and persons completes this book.